THE IMPORTANCE OF CROSS-CURRICULAR RELATIONS IN THE PROCESS FORMATION OF PROFESSIONAL ORIENTATION FUTURE TEACHERS OF NATURAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to intersubject relations in school system as well as in the system of higher education in selecting the contests for special subjects as one of the didactic conditions of new teachers' professional orientation in teaching subjects’.